Proposing the components of conceptual design model of iCAL4LA using comparative analysis method - Ahmad, Siti Zulaiha; Abdul Mutalib, Ariffin (Universiti Teknikal Malaysia Melaka, 2016)
This article discusses an ongoing study in determining the generic components for a conceptual design model of interactive computer-assisted learning that is specifically designed for low achieving (LA) children (iCAL4LA).These children need a specific learning support that can be used as an alternative material in their learning environment.In order to develop the conceptual model, this study extracts the common components from 15 strongly justified CAL studies. A comparative analysis has been conducted to determine the most appropriate components by using a set of specific classifications to prioritize the applicability.The results of the extraction process reveal 17 common components for consideration.Later, based on the pre-set justifications, 16 of them were selected as the proposed components for the Conceptual Design Model of iCAL4LA.In accordance, an initial model is proposed by considering those components.